2011
DOI: 10.1159/000334427
|View full text |Cite
|
Sign up to set email alerts
|

Doubly Committed Ventricular Septal Defect: Single-Centre Experience and Midterm Follow-Up

Abstract: Background: Doubly committed ventricular septal defect (dcVSD) is the least common type of VSD. Because published studies are rather scarce, this study aimed at evaluating the midterm outcome of dcVSDs. Methods: The records of all patients registered in the database of Paediatric and Congenital Cardiology, University Hospitals Leuven, with a dcVSD at 16 years of age were reviewed. Clinical, electrocardiographic and transthoracic echocardiographic changes from baseline, defined as of the age of 16 years, until … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The prevalence of moderate AR during follow-up after surgical VSD repair ranges from 2 to 17% in the literature, depending mainly on the type of VSD studied and the presence or absence of associated aortic valve malformations and/or surgery [10,14,21,28]. In unrepaired VSD, there is also a wide range of AR development, of between 2 and 20% [16].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of moderate AR during follow-up after surgical VSD repair ranges from 2 to 17% in the literature, depending mainly on the type of VSD studied and the presence or absence of associated aortic valve malformations and/or surgery [10,14,21,28]. In unrepaired VSD, there is also a wide range of AR development, of between 2 and 20% [16].…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that perimembranous and outlet VSDs have a higher spontaneous closure rate than previous studies. [ 17 20 21 22 ] The findings indicate that one out of every five outlet VSDs and one out of every two perimembranous VSDs tend to close spontaneously. This higher closure rate could be attributed to early diagnosis of VSD and longer follow-up duration in this cohort.…”
Section: Discussionmentioning
confidence: 97%
“…For several years, the popular way of differentiating the lesion from the much commoner variant, now usually described as being perimembranous [2] , was to consider the commoner form to be infracristal, whereas the lesion In this issue of Cardiology , Gabriels and colleagues [1] provide a superb account of the clinical evolution of patients born with a doubly committed ventricular septal defect. Their study is remarkable on several accounts.…”
mentioning
confidence: 99%